Economics and culture - Throsby, David (Cambridge University Press, 2001)
This book brings together two very disparate areas, economics and culture, considering both the economic aspects of cultural activity, and the cultural context of economics and economic behavior. The author discusses how cultural goods are valued in both economic and cultural terms, and introduces the concepts of cultural capital and sustainability. The book goes on to discuss the economics of creativity in the production of cultural goods and services; culture in economic development; the cultural industries; and cultural policy. An important topic analyzed in a stimulating and nontechnical style